2013
DOI: 10.1002/ange.201205260
|View full text |Cite
|
Sign up to set email alerts
|

Synthese fluorierter Bausteine durch Übergangsmetall‐vermittelte Hydrodefluorierungsreaktionen

Abstract: Die Aktivierung und Funktionalisierung von Kohlenstoff‐Fluor‐Bindungen ist eine der großen Herausforderungen für die metallorganische Chemie. Der steigende Bedarf an Wegen zur Einführung von Fluor in neue Materialien und biologisch aktive Moleküle hat die Entwicklung verschiedener Synthesestrategien inspiriert. Die Hydrodefluorierung wird als vielversprechender Ansatz angesehen, um teilfluorierte Bausteine aus leicht verfügbaren perfluorierten Basischemikalien zu gewinnen. Dieser Aufsatz fasst Aspekte zur Hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(13 citation statements)
references
References 209 publications
0
13
0
Order By: Relevance
“…[1] The second approach is the selective transformation of a specific carbon-fluorine bond of a perfluoro-or multifluoro-compound, which allows the preparation of organic compounds that include a fluorinated functional group. [2] In particular, the transformation of perfluoroarenes is an efficient and economical method for the preparation of highly functionalized organofluorine compounds and, therefore, a limited number of coupling reactions with aryl-metal compounds have been reported. [3][4][5][6][7][8][9] Radius et al reported the coupling reaction of octafluorotoluene (C 7 F 8 ) and perfluorobiphenyl (C 12 F 10 ) with aryl boronic acids in the presence of a catalytic amount of NHC-nickel(0) catalyst (NHC = N-heterocyclic carbene).…”
Section: Introductionmentioning
confidence: 99%
“…[1] The second approach is the selective transformation of a specific carbon-fluorine bond of a perfluoro-or multifluoro-compound, which allows the preparation of organic compounds that include a fluorinated functional group. [2] In particular, the transformation of perfluoroarenes is an efficient and economical method for the preparation of highly functionalized organofluorine compounds and, therefore, a limited number of coupling reactions with aryl-metal compounds have been reported. [3][4][5][6][7][8][9] Radius et al reported the coupling reaction of octafluorotoluene (C 7 F 8 ) and perfluorobiphenyl (C 12 F 10 ) with aryl boronic acids in the presence of a catalytic amount of NHC-nickel(0) catalyst (NHC = N-heterocyclic carbene).…”
Section: Introductionmentioning
confidence: 99%
“…[2d] Nevertheless,t hese methods usually suffer from relatively harsh reaction conditions and limited substrate scope.T oo vercome these problems,r ecent research has paid more attention to the transition-metalcatalyzed allylic selective CÀFb ond activation of polyfluorinated molecules. [9] Fore xample,F ujii [10] and co-workers once described an interesting chemo-and stereoselective synthesis of (Z)-fluoroalkenes through Pd-catalyzed allylic C À Fb ond activation of allylic gem-difluoride,w hereas Paquin [11] et al reported the palladium-catalyzed allylic amination of 3,3-difluoropropenes toward the synthesis of 3fluoroallylic amines (Scheme 1a). Note that both of the above processes initiate with the oxidative addition of an allylic C À F bond to apalladium(0) catalyst, and thus is limited by the high CÀFbond energies.…”
mentioning
confidence: 99%
“…[9] However, most of the reported methods are limited to reductive CÀF bond cleavage (hydrodefluorination), in which CÀC bonds are not formed. [10] This might be partially due to the fact that CÀF bonds are exceptionally strong (DH 298 CH 3 ÀF = 481 kJ mol À1 , DH 298 PhÀF = 532 kJ mol À1 ) [11] and unreactive. In general, highly reactive catalysts that are usually not compatible with other functional groups are required for the activation of CÀF bonds.…”
Section: Introductionmentioning
confidence: 99%